Итальянские мотивы в поэме Пушкина «Анджело» [Italian Motifs in Pushkin’s Poem _Andzhelo_] - Dolinin, Alexander (Slavica Revalensia, 2021)
Pushkin’s poem Andzhelo (1833) is based on the plot of Shakespeare’s Measure for Measure (1623). However, Pushkin changed the location from Vienna to “happy Italy,” and the article offers some explanations of the change. Besides the location and names of characters, the poem has no Italian ethnographic details but instead includes several allusions to Dante absent in Shakespeare. It seems that through them Pushkin amalgamated Dante and Shakespeare, providing an intertextual substitute for the Italian couleur locale.